2018
DOI: 10.1021/acssensors.8b00159
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Peptide-Based Biorecognition Elements for Biosensors Using in-Silico Evolution

Abstract: Sensors for human health and performance monitoring require biological recognition elements (BREs) at device interfaces for the detection of key molecular biomarkers that are measurable biological state indicators. BREs, including peptides, antibodies, and nucleic acids, bind to biomarkers in the vicinity of the sensor surface to create a signal proportional to the biomarker concentration. The discovery of BREs with the required sensitivity and selectivity to bind biomarkers at low concentrations remains a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…The terminal allene carboxamide functional group of the BAPTES ligand possesses high chemoselectivity toward the thiol side chain of Cys, and forms a stable and irreversible conjugate not prone to hydrolysis 36 . Importantly, instead of using antibodies to target cTnI, we chose a short, linear peptide evolved for high cTnI affinity by phage display and in silico evolution 37 . The use of peptides offers significant advantages for protein enrichment in comparison with antibodies, such as improved chemical stability to changes in pH and reducing environments, thermal stability, scalability using solid-phase peptide synthesis, and batch-to-batch reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…The terminal allene carboxamide functional group of the BAPTES ligand possesses high chemoselectivity toward the thiol side chain of Cys, and forms a stable and irreversible conjugate not prone to hydrolysis 36 . Importantly, instead of using antibodies to target cTnI, we chose a short, linear peptide evolved for high cTnI affinity by phage display and in silico evolution 37 . The use of peptides offers significant advantages for protein enrichment in comparison with antibodies, such as improved chemical stability to changes in pH and reducing environments, thermal stability, scalability using solid-phase peptide synthesis, and batch-to-batch reproducibility.…”
Section: Resultsmentioning
confidence: 99%
“…The binding affinity of P2 peptide was confirmed in our previous work by measuring the dissociation constants (K D ) of the P2 peptide or mAb in the presence of 114-141 troponin fragment or full-length troponin. 35 The K D of the peptide remained constant independent of troponin target (fragment or full length), while the K D of the antibody was 100-fold lowered using the troponin fragment lacking the N-terminus binding region. These results confirmed that the peptide and antibody binding domains were nonoverlapping.…”
Section: Synthesis and Characterization Of Pradamentioning
confidence: 96%
“…The P2 peptides (-WQIAYNEHQWQGGGC-), computationally evolved from a phage display peptide, had nanomolar binding affinity to cTnI. 35 The bioconjugation of P2 peptides to GNSs was achieved via Au-S linkage by introducing a cysteine residue at the C-terminus of the peptide. A tri-glycine spacer domain was inserted between the C-terminal cysteine and the P2 peptide to extend the binding domain away from the gold surface.…”
Section: Synthesis and Characterization Of Pradamentioning
confidence: 99%
See 1 more Smart Citation
“…EIS spectra were then acquired for each channel (up to 6 channels per experiment) with an AC RMS amplitude of 5 mV from 5000 Hz to 1 Hz. Analysis of each spectra was performed using software provided by Palmsens through fitting to a modified Randle's cell as done previously ( Figure S3) [37,38]. The resistance to charge transfer (R CT ) was recorded and further analyzed for each electrode in each condition.…”
Section: Electrochemical Measurements For Titrations Of Lysozymementioning
confidence: 99%